Is It a New Approach for Treating Senile Hypertension with Kidney-Tonifying Chinese Herbal Formula? A Systematic Review of Randomized Controlled Trials. (17th February 2014) - Wang, Jie; Xiong, Xingjiang; Yang, Xiaochen
Abstract : Objective . To assess the effect of kidney-tonifying (KT) Chinese herbal formula for senile hypertension (SH). Methods . A total of five databases (CENTRAL, Pubmed, CBM, CNKI, and VIP) were searched for published and unpublished randomized controlled trials (RCTs) up to November 30th, 2013. We included RCTs that confoundedly addressed the effect of KT formula in the treatment of SH. Results . Six studies involving 527 people were included. There was no evidence that KT formula alone had superior effects to antihypertensive drugs in systolic blood pressure (MD: −3.70 (−11.47, 4.07); P = 0.35 ) and diastolic blood pressure (MD: −3.00 (−7.26, −1.26); P = 0.17 ). However, there was evidence that KT formula combined with antihypertensive drugs was a better treatment option than antihypertensive drugs alone in systolic blood pressure (WMD: −8.69 (−12.35, −5.02); P < 0.00001 ) but no significant difference in diastolic blood pressure (WMD: −1.32 (−7.93, −5.30); P = 0.7 ). In addition, after several weeks of treatment, the level of blood lipid, endothelin, blood urea nitrogen, and creatinine decreased significantly (P < 0.05 ). Conclusion . Compared with antihypertensive drugs alone, KT formula combined with antihypertensive drugs may provide more benefits for patients with SH. The large-scale high-quality trials are warranted in future.